2017
DOI: 10.1038/srep43385
|View full text |Cite
|
Sign up to set email alerts
|

Storage of passive motion pattern in hippocampal CA1 region depends on CaMKII/CREB signaling pathway in a motion sickness rodent model

Abstract: Sensory mismatch between actual motion information and anticipated sensory patterns (internal model) is the etiology of motion sickness (MS). Some evidence supports that hippocampus might involve the neural storage of the “internal model”. This study established an “internal model” acquisition-retention behavioral model using a repeated habituation rotation training protocol. We tried to identify the hippocampal subregion involved in “internal model” retention using chemical lesion methods. Hippocampal kinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 62 publications
2
22
0
1
Order By: Relevance
“…It was found that mice belonging to the MS group exhibited a higher score compared with the control groups NC and MNT50. This indicates that rotation increased piloerection, urination, tremor, and defecation in MS group which resembles earlier published reports (Qi et al., 2019; Wang et al., 2017; Zheng et al., 2014; Zhou et al., 2017). Pretreatment with MCD and MNT exhibited a reduction in the score of the symptoms (Figure 3b).…”
Section: Discussionsupporting
confidence: 90%
“…It was found that mice belonging to the MS group exhibited a higher score compared with the control groups NC and MNT50. This indicates that rotation increased piloerection, urination, tremor, and defecation in MS group which resembles earlier published reports (Qi et al., 2019; Wang et al., 2017; Zheng et al., 2014; Zhou et al., 2017). Pretreatment with MCD and MNT exhibited a reduction in the score of the symptoms (Figure 3b).…”
Section: Discussionsupporting
confidence: 90%
“…Because of the possibility to use genetically-engineered mice and to conduct molecular studies, rodent models have recently attracted the attention of many research groups. Wang et al ( 44 46 ) have studied in rats the inter-individual differences and the implication of the vestibulo-thalamic pathway in the habituation to provocative rotation . They also demonstrated that otoconia-deficient mice (het) are less susceptible to vestibular MS, indicating the pivotal role of otolithic overstimulation in MS generation.…”
Section: Discussionmentioning
confidence: 99%
“…The Ferris wheel-like rotation device was modified based on the one created by Crampton and Lucot ( 1985 ) and has been used to establish MS rat model in our previous studies (Wang et al, 2012 , 2017 ; Zhang et al, 2016 ; Zhou et al, 2017 ). It is composed of two plexiglass boxes suspended on two metal frames.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of stroboscopic light synchronized or unsynchronized to the acceleration–deceleration phase of rotation were examined, and the influence of color temperature and lighting intensity was also observed. MS-related gastrointestinal responses were assessed by measuring conditioned gaping and defecation responses due to the absence of vomiting reaction in rodents (Wang et al, 2012 , 2017 ; Zhou et al, 2017 ; Qi et al, 2019 ; Devuono et al, 2020 ). Motor and balance performance were evaluated using spontaneous locomotion test and balance beam test (Manno et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%